The Effectiveness of Talk Show Radio Dikmas Lantas by Dikyasa Units in Reducing Traffic Violations in the Legal Area of Polresta Pekanbaru - Dwiwahyu Sagit Ramadhan Sunarto (Indonesian Journal of Police Studies, 2021)
Traffic violations are a problem that has been widespread in Pekanbaru City, starting from the diversity of cultures that make people have their own thoughts in taking action without thinking about the applicable rules. In preventing this, the traffic unit is through the implementation of the Traffic Dikmas, which aims to deliver traffic education to the public so that the public understands good and orderly traffic procedures. In the discussion of this thesis the writer uses the theory of Management (POAC), Management (6M), Traffic Violation, the Concept of Effectiveness, Dikmas Lantas, as an analysis knife to discuss the findings and research problems. This study uses a qualitative approach and the type of research is field research. The research focus is on the Dikyasa Unit Traffic Unit at the Pekanbaru Police with the community in Pekanbaru City as the source of document data, then the validity of the data is proven by data triangulation. Data analysis techniques were data reduction, data presentation and conclusion drawing. The results of the study found that the traffic violations of the people of Pekanbaru City increased from year to year. Efforts to prevent community traffic violations which are analyzed using management theory are to make safety appeals when 9 Dikmas activities have not been effective. The inhibiting factors are human resources, time and place, community attention and support, while the supporting factors are budget and cross-sectoral cooperation. Even though the Dikmas Traffic activities have been carried out to prevent traffic violations, the people of Pekanbaru City often commit traffic violations. Based on the research results, various efforts have been made to prevent traffic violations. The author suggests providing vocational education (Dikjur), adding personnel, and adding sarpras to support Dikmas Lantas activities in order to encourage community compliance to comply with applicable regulations.